2022
DOI: 10.1136/tobaccocontrol-2021-057135
|View full text |Cite|
|
Sign up to set email alerts
|

Youth tobacco use before and after flavoured tobacco sales restrictions in Oakland, California and San Francisco, California

Abstract: The tobacco industry has used recent findings from the Youth Risk Behavior Surveillance System Survey (YRBSS) to claim that a sales restriction on flavoured tobacco products might increase youth combustible cigarette use. In this special communication, we examined YRBSS data and reached the opposite conclusion. We observed the patterns in youth cigarette smoking in Oakland, California following its 2017 convenience store flavoured tobacco sales restriction. We also found that 2019 YRBSS data from San Francisco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…She found that the ban was associated with a doubled odds of recent cigarette smoking among high school students relative to control districts (adjusted odds ratio: 2.24). A critique [ 35 ] argued that the data used in the study was collected prior to enforcement of the restriction and, as such, considered it an inaccurate representation of the restriction’s impacts. Instead, the authors pointed to neighbouring Oakland, CA, which saw a purported decline in high school youth vaping and cigarette use from 2017 to 2019 following the July 2018 ban on convenience store flavoured ENDS sales.…”
Section: Resultsmentioning
confidence: 99%
“…She found that the ban was associated with a doubled odds of recent cigarette smoking among high school students relative to control districts (adjusted odds ratio: 2.24). A critique [ 35 ] argued that the data used in the study was collected prior to enforcement of the restriction and, as such, considered it an inaccurate representation of the restriction’s impacts. Instead, the authors pointed to neighbouring Oakland, CA, which saw a purported decline in high school youth vaping and cigarette use from 2017 to 2019 following the July 2018 ban on convenience store flavoured ENDS sales.…”
Section: Resultsmentioning
confidence: 99%
“…Given the limited effectiveness of e-cigarettes as adult smoking-cessation devices [ 40 , 41 ] and the role of flavors in promoting adolescent e-cigarette use [ 6 , 30 , 34 ], the FDA should adopt more comprehensive policies that prohibit all flavors, including menthol, in all types of e-cigarette devices to help achieve its stated goal of stopping the public health crisis of adolescent e-cigarette use [ 12 ]. Furthermore, states and localities may consider enacting policies to limit or ban e-cigarette flavors, a strategy that has been associated with reductions in e-cigarette retail sales at the city level [ 37 , 42 ]. It should be noted, however, that local policies that restrict retail sales of flavored e-cigarettes may not prevent underage access through alternative sources, such as online purchases or social sources such as friends [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Progress in this domain may facilitate more tailored prevention strategies. Similarly, future research should more closely examine how patterns of e-cigarette use following the FDA’s 2020 prioritized enforcement may vary based on geographic region and in response to local attitudes and policies such as flavor bans [ 37 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Data from the UK after implementation of the European Union menthol cigarette ban (Kock et al 17 ) show that while the proportion of menthol smokers declined, a substantial minority still reported menthol use 1 year later, suggesting the continued availability of menthol products or products designed to circumvent the ban, underscoring the need for continued monitoring. Liu et al 18 highlight challenges in short-term evaluation of the impacts of policy changes around flavoured tobacco products using publicly available data, in this case the timing of surveys relative to policy implementation.…”
Section: Flavoured Product Bans/restrictionsmentioning
confidence: 99%